Acute creatine monohydrate supplementation: A descriptive physiological profile of responders vs. nonresponders - Syrotuik, D. G.; Bell, G. J. (The Journal of Strength and Conditioning Research, 2004)
The purpose of this study was to describe the physiological profile of responders (>20 mmol·kg-1 dry weight [dw] increase in total intramuscular creatine monohydrate [Cr] + phosphorylated creatine [PCr]) versus nonresponders (<10 mmol·kg-1 dw increase) to a 5-day Cr load (0.3 g·kg-1·d-1) in 11 healthy men (mean age = 22.7 years). Pre-post 5-day cellular measures included total resting Cr content (Cr + PCr), fiber type composition, and fiber type cross-sectional area (CSA) determined from muscle biopsies of the vastus lateralis. Body mass, daily dietary intake, 24-hour urine outputs, urinary Cr and creatinine (CrN), and strength performance measures (1 repetition maximum [1RM] bench and leg press) were also assessed before and after the 5-day loading period. Results indicated that there were 3 levels of response to the 5-day supplementation: responders (R), quasi responders (QR), and nonresponders (NR) with mean changes in resting Cr + PCr of 29.5 mmol·kg-1 dw (n = 3), 14.9 mmol·kg-1 dw (n = 5), and 5.1 mmol·kg-1 dw (n = 3), respectively. The results support a person-by-treatment interaction to acute Cr supplementation with R possessing a biological profile of lowest initial levels of Cr + PCr, greatest percentage of type II fibers, and greatest preload muscle fiber CSA and fat-free mass. Responders also showed improvement in 1RM leg press scores following the 5-day loading period. NR had higher preload levels of Cr + PCr, less type II muscle fibers, small preload muscle CSA, and lower fat-free mass and displayed no improvements in 1RM strength scores. The results suggest that to be considered a responder to acute oral supplementation, a favorable preexisting biological profile may determine the final extent to which an individual responds to supplementation. Physiologic profiles of nonresponders appear to be different and may limit their ability to uptake Cr. This may help partially explain the reported equivocal performance findings in the Cr supplementation literature.